The Role of Teacher Professional Development, Instructional Leadership, and Organizational Culture on Teaching Performance - A. Idun Suwarna; M. Makhrus Ali; Dina Destari; Ilyas (Malaqbi Publisher, 2026)
Teacher performance plays a crucial role in determining the quality of teaching and learning in schools. Improving teaching performance requires not only individual teacher competence but also supportive leadership, continuous professional development, and a positive organizational environment. This study aims to examine the roles of teacher professional development, instructional leadership, and organizational culture in influencing teaching performance. Using a quantitative approach, data were collected through a structured questionnaire from teachers in formal educational institutions. The data were analyzed using Structural Equation Modeling with the Partial Least Squares technique (SEM-PLS). The results indicate that teacher professional development, instructional leadership, and organizational culture each have a positive and significant effect on teaching performance. Among these factors, instructional leadership emerged as the strongest predictor, highlighting the central role of school leaders in shaping instructional quality. Teacher professional development was also found to significantly enhance teaching performance by improving instructional competence and professional capacity, while organizational culture contributed by fostering collaboration, trust, and shared commitment among teachers. These findings suggest that teaching performance can be effectively enhanced through an integrated approach that aligns professional learning opportunities, leadership practices, and supportive organizational cultures. The study offers practical implications for school leaders and policymakers in designing strategies to improve teacher effectiveness and educational quality.